Golden Network / Nuraida Syamimi Mohd Azuki - Mohd Azuki, Nuraida Syamimi (2020)
To do a case study for the sake of Fundamental of Entrepreneurship (ENT300) course requirement, me and classmates must do an individual task. This case study required us to find a company that have less than RM250000 as an annual sales. So that, we need to collect all the informations about a company that we choosed. I have decided to do case study on a company which is Golden Network. Golden Network is a printing and souvenirs business. During pandemic COVID-19, I could not arranged a face to face interview, so that I took an initiative by contact Golden Network to do a telephone interview. In addition, I had also did some research from Google to find more information about Golden Network. From the interview and research, I had known about their entrepreneur and business profile and also entrepreneurial characteristics. Moreover, the reason why I choose Golden Network is because it is a small business that suitable for the task that given by my lecturer. Business entity for Golden Network is sole proprietorship. Sole proprietorship is owned and run by one person and in which there is no legal distinction between owner and the business entity. The owner is in direct control of all elements and is legally accountable for the finances of the business may include debts, loans and loss.